Participation of university community members in Health Promoting University (HPU) initiatives - Mónica Suárez-Reyes; Stephan Van den Broucke (Frontiers Media S.A., 2023)
BackgroundSeveral universities around the world have adopted the settings approach to health to create a Health Promoting University (HPU) initiative. Health promoting initiatives are built on the values of health promotion, with participation being one of the most important. Despite the above, there is little information on how university community members participate in HPU initiatives. This study aims to describe the participation of university community members in HPU initiatives in universities around the world.MethodsAn online questionnaire was sent to representatives of universities that have implemented a HPU initiative. The questionnaire inquired about the level and nature of participation of university community members (students, professors, and administrative/technical staff) at different levels. Three levels of participation ranged from lower to higher levels were considered: (a) information delivery strategies; (b) consultation strategies and (c) involvement in design, planning and decision-making processes.ResultsAt least the 50% of the universities implemented strategies so that all the members of the community could participate at all levels. Information delivery strategies were the most often used, with students being the main target group. Consultation strategies were aimed mainly at students and professors, whilst professors participated most actively in the design, planning and decision-making.ConclusionDifferent participation strategies are used in the HPU initiatives. Information delivery strategies, which represent the lowest level of participation, were the most often reported. Higher levels of participation were less used in the HPU initiatives. HPU initiatives should seek for strategies to provide more high-level participation to all university community members.